The review of gamification learning methods on PE teaching in primary school through adaptive perspective - Yuan, Wei; Samsudin, Shamsulariffin; Abdullah, Borhannudin; Farizan, Noor Hamzani; Hassan, Muhammad Zarif; Ji, Cheng (Creative Publishing House, 2024)
The purpose of this study is to explore the value implication and practice path of gamification transformation of primary school physical education under the perspective of adaptive education. From the perspective of adaptive education, the gamified transformation of primary school physical education has many values, such as improving learning motivation, enhancing learning interest, promoting subject exchange, cultivating will quality, promoting independent learning, benefiting physical and mental health and promoting personality development. However, in reality, there are also problems such as lack of differences in teaching content, lack of innovation in teaching methods, lack of integration ability of disciplines, lack of effective evaluation system, lack of teaching resources, high academic pressure, parents' cognitive bias and social cognitive bias. Therefore, we can promote the gamified transformation of primary school physical education by changing teachers' ideas, enhancing teacher training, enriching curriculum design, improving evaluation mechanism, increasing resource input, reducing students' burden, guiding parents' cognition and cultivating social atmosphere, and so on, so as to promote the all-round development of students.